Safeguarding intangible assets - Moberly, Michael D. (Butterworth-Heinemann, 2014)
Provides strategies for preserving and enhancing a company's intangible assets such as patents, trademarks, copyrights, methodologies, and brand to increase its profitability, competitiveness, and sustainability.